MODEL PENYELENGGARAAN PENDIDIKAN DALAM ISLAM - H. Abdul Wahab Syakhrani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The quite diverse education model in the world of education provides its own teaching and justification, that the education delivery model has two kinds, namely Islamic education and general education. From the two educational models, it also provides an understanding of the history of educational institutions that have been formed for generations known as the curriculum